Willingness to pay of local visitors to the recreational services of the Huajsapata natural viewpoint, Puno – Peru (Gestionar: revista de empresa y gobierno, 2023)
The research was carried out with the objective of estimating the willingness to pay (WTP) of local visitors to the passive recreational services of the natural viewpoint called "Cerrito de Huajsapata" (Puno - Peru) in a hypothetical case of improvement of services. A quantitative approach was followed, through the survey technique, applying the contingent valuation method to a probabilistic sample of 383 local visitors who belong to the working-age population (WAP). The results show, according to the calculation of the DAP in Soles (S/) that local visitors would be willing to pay S/1.00 to access the improved recreational services, but if this rate were increased by one sol, the DAP has a probability of increasing by 47% since a tourist service leads to the expectations of improvement of said service; however, it must be taken into account that said increase has a limit. Therefore, there is a predisposition by local visitors to pay for access to the recreational services of the natural viewpoint of "Cerrito Huajsapata" as long as these services are improved.
Keywords: willingness to pay; natural viewpoint; tourist service; contingent valuation